2012
DOI: 10.1007/s10886-012-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Identification, Emission Pattern and Function of Male-Specific Pheromones Released by a Rarely Swarming Locust, Schistocerca americana

Abstract: Pheromones serve key functions in the biology of swarming locusts. However, research has focused largely on the mass-swarming desert locust, Schistocerca gregaria. We extended these investigations to the pheromonal profile of the rarely swarming American bird grasshopper, S. americana (Drury). The headspace of mature gregarious S. americana males contained three characteristic electroantennogram-active components: (Z)-3-nonen-1-ol, (Z)-2-octen-1-ol, and nonanal. These substances were accompanied by aromatics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In the desert locust, the remarkable change between the solitary and the gregarious phase seems to be controlled by signaling compounds 1 . Thus, in Schistocerca gregaria , pheromones probably do not only play a central role in the reproduction process 31 , 32 but also may be essential for the phase change. In line with the existence of various pheromonal compounds for eliciting different behaviors or priming diverse physiological effects in desert locusts, our two-color FISH experiments revealed further SgreOR types that alike the b-OR group members were co-expressed with SNMP1 and thus can also be considered as candidate pheromone receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the desert locust, the remarkable change between the solitary and the gregarious phase seems to be controlled by signaling compounds 1 . Thus, in Schistocerca gregaria , pheromones probably do not only play a central role in the reproduction process 31 , 32 but also may be essential for the phase change. In line with the existence of various pheromonal compounds for eliciting different behaviors or priming diverse physiological effects in desert locusts, our two-color FISH experiments revealed further SgreOR types that alike the b-OR group members were co-expressed with SNMP1 and thus can also be considered as candidate pheromone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In marked contrast to lepidopteran and dipteran species, the mechanisms of pheromone signaling in hemimetabolic insects are largely elusive although some pheromonal compounds have been identified in locusts 26 - 32 . The hemimetabolic locusts are only distantly related to holometabolic insects 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pheromones mediating courtship–inhibition have been observed in Schistocerca gregaria ( Seidelmann and Ferenz 2002 , Seidelmann et al. 2003 ) and the related species Schistocerca americana ( Stahr et al. 2013 ).…”
mentioning
confidence: 99%
“…Other mechanisms that can affect pheromone production and release are pathogens [19], volatiles from host plants [31], conspecifics [35,36], or prey [37]. Verheggen et al [37] recently found that pheromone production in the Asian lady beetles (Harmonia axyridis) (Figure 1A) is conditioned by the presence of prey, as exposure to volatiles of the prey initiated pheromone production.…”
Section: Glossarymentioning
confidence: 99%